A study on compliance of seat belt usage among car users in district of Shah Alam, Selangor / Izah Othaman - Othaman, Izah (Bachelor of Science (Hons.) Statistics, 2015)
Despite of its effectiveness in increasing seatbelt use, limited studies were conducted to study on a compliance of seat belt usage among car users. The aim of this study is to identify the factors that influenced car users to wear seat belt. In addition, the factors that associated to the seat belt usage also were studied. A study was conducted in district of Shah Alam. A total of 151 respondents were interviewed to complete this study. A self-administered questionnaire were given to them to give their perception toward seat belts Approximately, 67.5% of the respondents reported that they are “Always/often” wore seat belt meanwhile 32.5% of the respondents reported that they are “occasionally/rarely” wore seat belt. The most common reason if they are wearing seat because “it is a law”, “avoid serious injury” and “fear of getting summons” ,while if they are not using seat belt because of “ I am only driving in a short distance”, “I forgot to put it on” and “I am in a rush”. Statistical test such as Chi-Square of Association, Logistic Regression and Discriminant Analysis have been performed. Females (61.8%) are more likely to wear seat belt compare to male (38.2%) car users as have been proved by the Chi-square test. Logistic Regression and Discriminant were done to compare the less error rate as to choose the function model. Since Logistic Regression has a lower error rate which is (29.1%) compare to Discriminant Analysis (31.1%), therefore Logistic Regression was chosen. It also important to note that the car users that always/often using seat belt with a factor of attitude is 2.082 times more likely to wear seat belt compare to the car users that occasionally/rarely wearing seat belt. This study is essential in understanding the Malaysian tendency in belting up while being occupied in a vehicle. The factor highlighted in this study should be emphasized on road safety education in order to increase seat belt wearing rate in this country and ultimately to preventing deaths due to road crashes